Risk factors determining bile leakage after multiple liver hydatid cyst surgery - Özdemir, Yılmaz; Ozer, İlter and Sürmelioğlu, Ali and Dalgıç, Tahsin and Aksoy, Erol and Çaparlar, Mehmet Ali and Ulaş, Murat and Özoğul, Yusuf Bayram and Bostancı, Erdal Birol and Akoğlu, Musa (Journal of Surgery and Medicine, 2022)
Background/Aim: Biliary leaks are the main source of morbidity after liver hydatid cyst surgery. Many identified factors have been examined in predicting biliary leaks. The aim of this study was to determine the postoperative bile leakage rate and predictive factors affecting bile leakage in multiple liver hydatid cysts. Method: In our retrospective cohort study, the data of 130 patients who underwent multiple liver hydatid surgery in our clinic between January 2007 and November 2013 were analyzed. Results: In the 130 patients with multiple cysts, 323 hydatid cysts were detected. The number of cysts was 2 in 65.4% of the patients, and 3 or more in 34.6% of the patients. The postoperative bile leakage rate was 19.2%. According to the univariate analyses, during the preoperative period, the presence of jaundice, fever, leukocytosis, eosinophilia, aspartate aminotransferase, alanine aminotransferase, gamma glutamyl transferase, alkaline phosphatase, and direct bilirubin increase, the largest cyst being located in the perihilar region, the mean diameter of the cyst, the diameter of the largest cyst, biliary tract dilatation on the preoperative images, and infection were associated with increased postoperative bile leakage. In the multivariate analyses, eosinophilia and biliary tract dilatation on the preoperative images were found to be independent risk factors for postoperative bile leakage. Conclusion: In this study, the most determining factors for bile leakage after multiple liver hydatid cyst surgery were a high eosinophil rate and the presence of dilatation in the biliary tract on the preoperative radiological images.